Answer:
Step-by-step explanation:
Any expression that says (2 * 4)/3 is correct, even though there is a shift in the brackets. That means that A, B, C are all the same thing, and all are correct.
Only D is lying.
2*(1/3) = 2/3
4*(1/3) = 4/3 Now we have to add them
2/3 + 4/3 = 6/3 = 2
To show what the real answer is, try A
2*4/3
8/3 is the actual answer.
Answer:
d is the answer
Step-by-step explanation:
Answer:
C should be your answer if I'm not right then forgive me please.
Step-by-step explanation:
Solve for x by simplifying both sides of the equation then isolating teh varible.
your answer = - 1/7
Answer:
You're correct.
Step-by-step explanation: